The Russian Far East in a Post Cold War Environment, and New International Cooperation Plans - Sevastyanov, Sergey (Mongolian Journal of International Affairs, 2014)
No abstract available DOI: http://dx.doi.org/10.5564/mjia.v0i7.141 The Mongolian Journal of International Affairs; Number 7, 2000, Pages 63-72